2015
DOI: 10.1002/2015jb011985
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying hydrate solidification front advancing using method of characteristics

Abstract: We develop a one‐dimensional analytical solution based on the method of characteristics to explore hydrate formation from gas injection into brine‐saturated sediments within the hydrate stability zone. Our solution includes fully coupled multiphase and multicomponent flow and the associated advective transport in a homogeneous system. Our solution shows that hydrate saturation is controlled by the initial thermodynamic state of the system and changed by the gas fractional flow. Hydrate saturation in gas‐rich s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Liu and Flemings (2007) quantitatively explained these observations with a fully coupled multiphase flow, multicomponent transport and energy conservation numerical model. In this model, hydrate saturation is influenced by the direction of free gas flow, with less hydrate formed for vertically upward flow and more for vertically downward flow (You, DiCarlo, et al, 2015;You et al, 2016). Latent heat and salt exculsion from hydrate formation becomes very important in systems with high methane flux where hydrate formation rates are high (e.g., Smith, Flemings, Liu, et al, 2014).…”
Section: Bulk Thermodynamic Equilibrium-based Modelmentioning
confidence: 99%
“…Liu and Flemings (2007) quantitatively explained these observations with a fully coupled multiphase flow, multicomponent transport and energy conservation numerical model. In this model, hydrate saturation is influenced by the direction of free gas flow, with less hydrate formed for vertically upward flow and more for vertically downward flow (You, DiCarlo, et al, 2015;You et al, 2016). Latent heat and salt exculsion from hydrate formation becomes very important in systems with high methane flux where hydrate formation rates are high (e.g., Smith, Flemings, Liu, et al, 2014).…”
Section: Bulk Thermodynamic Equilibrium-based Modelmentioning
confidence: 99%
“…With continual gas supply, hydrate forms until the local salinity is elevated to the three‐phase concentration (Liu & Flemings, ; You, DiCarlo, et al, ), which occurs at the three‐phase (gas, liquid, and hydrate) equilibrium hydrate saturation ( S heq ). At three‐phase equilibrium, hydrate formation is limited and gas migrates farther into the GHSZ (Liu & Flemings, ; Torres et al, ; You, DiCarlo, et al, ). This process produces an upward‐propagating hydrate formation front with hydrate, gas, and water present at three‐phase equilibrium conditions behind the front and brine at initial salinity present ahead of the front.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, gas migrates updip into the GHSZ, forming hydrate (Liu & Flemings, 2006;Torres et al, 2004;Tréhu et al, 2004) and elevating the local pore fluid salinity (Hesse & Harrison, 1981;Torres et al, 2004;Ussler & Paull, 2001). With continual gas supply, hydrate forms until the local salinity is elevated to the three-phase concentration (Liu & Flemings, 2007;You, DiCarlo, et al, 2015), which occurs at the three-phase (gas, liquid, and hydrate) equilibrium hydrate saturation (S heq ). At three-phase equilibrium, hydrate formation is limited and gas migrates farther into the GHSZ (Liu & Flemings, 2007;Torres et al, 2004;You, DiCarlo, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Models further suggested that the formation of concentrated hydrate deposits commonly relied on focused migration of either microbial methane or thermogenic natural gas, often as a free gas phase through interconnected permeable strata, faults, and fracture zones. Focused migration of gas is considered to be a major process leading to the formation of prospective hydrate accumulations in sandstones Liu & Flemings, 2007;You et al, 2015). However, concentration of hydrate may also be achieved through continuous recycling of methane related to sedimentation or tectonic uplift, resulting in relative upward migration of the base of gas hydrate stability (BGHS), dissociation of hydrates and re-incorporation of gas into newly-formed hydrate above (Bünz et al, 2003;Burwicz et al, 2017;Crutchley et al, 2018;Paull et al, 1994;Rempel & Buffett, 1997) In this study, we investigate mechanisms for gas hydrate formation and resulting hydrate distribution using a 3-D model of the southern Hikurangi Margin, New Zealand (Figure 1).…”
Section: Introductionmentioning
confidence: 99%